아버지의 역할수행과 아동 및 청소년의 사회성 - 송요현(Yo Hyun Song); 현온강(On Kang Hyun) (Korean Journal of child studies, 2006)
This study examined relationships between children's perceptions of fathering practice and their sociality. The subjects were 569 grade 6 students and 511 grade 3 students in Seoul and Gyeonggi-do. Major results showed (1) the effectiveness of quantity; that is, children's sociality increased with increase in fathering practice. (2) The coefficient of correlation between fathering practice and children's sociality was higher in middle childhood than in early adolescence. (3) Children's sociality was influenced by child variables and fathering practice variables, especially more by the variables of Fathering Practice. Among the variables of Fathering Practice Scales, the variable of "Education of children" is the most influential element for improving "Children's Sociality".